STUDI HABITAT POHON GOFASA (Vitex cofassus) DI PULAU MARSEGU SERAM BAGIAN BARAT - Makatita , Hartina; Siahaya, Ludia; Sahupala, Andjela (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The aim of this research is to determine the habitat conditions of the Gofasa tree (Vitex cofassus) on Marsegu Island, West Seram. The data used was obtained from observations or collection in the field in the form of measurements of the height and diameter of Gofasa trees and other supporting data. In this research, data analysis was carried out descriptively using a quantitative approach, namely a method that aims to describe systematically and factually the facts and relationships between the variables studied through collecting, processing and analyzing data. The condition of the Gofasa habitat is also described based on data from observations and recording in the field. The results of the research show that the Gofasa trees that grow on Marsegu Island are in the coral secondary forest type with good light intensity and grow in areas with dry soil moisture and a temperature of 27°C. It is hoped that there will be further research on the distribution patterns and growth places of Gofasa trees on Marsegu Island. It is hoped that this research can be useful in protecting and preserving the Gofasa wood species in Maluku.